An Evaluation of the Contemporary Uses and Cultural Significance of Mammals in Mexico - Dulce María Ávila Nájera; Eduardo J Naranjo; Barbara Jane Tigar; Oscar Agustin Villarreal; Germán David Mendoza (Ethnobiology Letters, 2018)
We evaluated current uses of wild mammals by indigenous and mestizo communities in Mexico by extracting data from 59 sources published or produced between 1987–2017, covering data from 240 localities and 3,905 questionnaires. We then calculated a Cultural Value Index (CVI) previously applied to plants to quantify resource use and assess the cultural significance of each mammal. A total of 82 species were reported, and the animals with the highest cultural importance according to their CVI (in brackets) were two species of deer (Odocoileus virginianus [18.32] and Mazama temama [10.04]), as well as the nine-banded armadillo (Dasypus novemcinctus [14.18]), white-nosed coati (Nasua narica [14.75]), collared peccary (Pecari tajaccu [11.90]), northern raccoon (Procyon lotor [11.28]) and spotted paca (Cuniculus paca [9.84]). The most common uses were for food, to reduce the damage or harm they cause, and for medicinal purposes, with O. virginianus, P. lotor, N. narica, and D. novemcinctus frequently hunted for all these reasons. Our analysis also highlighted the hunting of rarer species of national conservation concern, including commercial trading of body parts of the felids Panthera onca, Leopardus pardalis, and Leopardus wiedii. By quantifying the ethnozoological significance of wildlife to indigenous communities, indices such as CVI provide a robust measure of the extent of use and preference for particular species or taxa. This adds to the body of evidence used to develop effective regulations and laws related to harvesting and hunting, and helps promote a more sustainable and long-term approach to the use of natural resources.